Mathematical Modelling of Longitudinal Vibration on Propulsion System 5200 DWT General Cargo Ship - Benedicta Dian Alfanda; Adi Wirawan Husodo; Intan Rahmahwati; Febry Yulistiawan (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
The vibration level of the propulsion system will change during its operation. This vibration is caused by harmonic excitation forces produced by the rotation of the main engine and propeller shaft. Ship propulsion systems experience longitudinal, torsional and lateral vibrations. Excessive vibration will produce noise and reduce engine performance. Vibrations can also cause resonance in the system, which can be fatal and damage the structure. The excitation frequency value is close to or equal to the natural system frequency, which causes resonance. This paper has identified the vibration response of the propulsion system by using numerical software through mathematical modelling governed by ABS. In addition, the total vibration response was obtained using the modal analysis method by summing up the contributions of each mode. The excitation source generated is due to the rotation of the main engine. Ultimately, the response obtained will be adjusted to the standard class. The modelling results obtained a 3-Degree-of-Freedom forced vibration model consisting of three masses and three springs. The resulting response values are displacement and velocity, where the highest response occurs at 347 rpm with a deviation of ±0.1345 mm to ±0.3371 mm and a velocity value of ±4.8847 mm/s to ±12.2424 mm/s. The slightest response occurs at 459 rpm with a deviation range of ±0.0034 mm to ±0.0050 mm and velocity values of ±0.1634 mm/s to ±0.2382 mm/s. Based on all the results of adjusting the vibration response value with the ABS class vibration limit graph, the vibration is still below the permissible threshold line.